Analysis of The Influence of Instructional Design and Usability on Student Motivation in Online Tutoring - Nofri Rhamawati; Sumarsono (Kaunia: Integration and Interconnection Islam and Science Journal, 2022)
Learning in the online era is not a barrier for tutoring institutions in providing online services. However, from the user's perspective, there is an inhibiting factor, namely decreased learning motivation when using online learning platforms. One of the aspects is usability and instructional design. In particular, students' approaches to learning through online tutoring systems were examined. Students from various types of education participate in this course namely junior high students, high school students, vocational high school students, universities and the general public. Using a qualitative research approach that examines data from the perspective of student experience. The study found that the completeness and clarity of instructional design had a dominant factor in influencing students' learning motivation. While the usability aspect is not significant enough in influencing the learning motivation of tutoring